Integrated reservoir studies for CO2-enhanced oil recovery and sequestration : application to an Indian Mature Oil Field - Ganguli, Shib Sankar (Springer, 2017)
This book addresses the feasibility of CO2-EOR and sequestration in a mature Indian oil field, pursuing for the first time a cross-disciplinary approach that combines the results from reservoir modeling and flow simulation, rock physics modeling, geomechanics, and time-lapse (4D) seismic monitoring study. The key findings presented indicate that the field under study holds great potential for enhanced oil recovery (EOR) and subsequent CO2 storage. Experts around the globe argue that storing CO2 by means of enhanced oil recovery (EOR) could support climate change mitigation by reducing the amount of CO2 emissions in the atmosphere by ca. 20%. CO2-EOR and sequestration is a cutting-edge and emerging field of research in India, and there is an urgent need to assess Indian hydrocarbon reservoirs for the feasibility of CO2-EOR and storage. Combining the fundamentals of the technique with concrete examples, the book is essential reading for all researchers, students and oil & gas professionals who want to fully understand CO2-EOR and its geologic sequestration process in mature oil fields.
"Doctoral thesis accepted by Academy of Scientific and Innovative Research."
Keywords: Carbon dioxide enhanced oil recovery.; Carbon sequestration.; elektronické knihy; electronic books